Personal Branding D_Kadoor untuk Menaikkan Pupolaritas melalui Instagram - Syahida, Amanah Rakhim; Qorib, Fathul (ARISTO, 2018)
The purpose of doing this research is to know how personal branding a person made by utilizing social media. Like the d_kadoor phenomenon of uploading a unique and unique video. In a number of videos shared by him, it looks Kadir Bachmid or d_kadoor behaving witty. Most imitate the behavior of mothers, ranging from clothing, style to the theme of gossip about arisan. Research on d_kadoor is a personal branding domain so that the theory used is personal branding. While the desired approach in this study is a qualitative approach with only one informant, namely Kadir Bachmid as d_kadoor itself. The results of this study illustrate that personal branding can show popular (famous) people. With the following strategies: 1) social media as a primary need. 2) Creative, inofatif, and have high confidence in Social Media For Personal Branding.3) Sensitive to information that is becoming a trend in society.4) Be entertaining.5) Non verbal and verbal communication has an identity.